GINGIVAL TISSUE MICROCIRCULATION FEATURES IN PATIENTS WITH INCISOR CROWDING - D. A. Domenyuk; A. G. Karslieva; E. G. Vedeshina; S. V. Dmitrienko; A. S. Kochkonyan; Yu. S. Arutyunyan (Фармация и фармакология (Пятигорск))
Morphological parameters of the capillaries (diameter, linear and volumetric bloodflow rate, capillary network density) were evaluated in children and adolescents aged 12 to 15 years with normal occlusion and dentoalveolar anomalies using the computer capillaroscopy device KK 4-01 (“TSAV” JSC Center “Analiz veschestv”). We have also carried out a visual assessment of the microcirculation. The patients with jaw-bones hypoplasia and crowded teeth revealed deeper location of the arterioles and venules and reduced morphometric parameters of tissue blood flow, thus it indicates signified rheological disorders at the early stages of atrophic processes in the periodontal tissues.